Enhanced dropwise condensation of low surface tension fluids - Tan, Jillesa Li Rong (Nanyang Technological University, 2023)
This report investigates the dropwise condensation heat transfer performance of ethanol on additively manufactured aluminum alloy (AlSi10Mg), conventional aluminum (Al6061) and conventional copper surfaces treated with different methods to alter their surface energies. The aim is to determine the best surface treatment method to promote dropwise condensation of ethanol on additively manufactured surfaces by studying the condensation heat flux and determining the heat transfer coefficient. The experiments involved directing ethanol vapor onto the test surface and measuring the droplet distribution density to predict their heat transfer performance.